Combined Lipidomics and Network Pharmacology Study of Protective Effects of Salvia miltiorrhiza against Blood Stasis Syndrome. (19th March 2021) - Jin, Yidian; Xie, Zhiru; Li, Shasha; Zeng, Xiangyu; Wang, Leqi; Hu, Ping; Zhang, Hongyang; Xiao, Xue
Abstract : Blood stasis syndrome (BSS) is one of the most common symptoms of cardiovascular diseases (CVDs) in traditional Chinese medicine (TCM) theory. Previous studies have identified that Salvia miltiorrhiza (Danshen) has beneficial effects on BSS, but there is no relevant research from the perspective of lipidomics to study the mechanism of Danshen against BSS since hyperlipidemia has been the widely accepted risk factor of CVDs. In this study, lipidomics technology combined with network pharmacology was applied to investigate the pathological mechanism of BSS and the protective effects of Danshen. The lipidomics profiling based on the UPLC-QTOF-MS analysis method was applied to identify the differential metabolites in the plasma of blood stasis rats. The related pathway and potential targets involved in the anti-BSS effects of Danshen were predicted by pathway analysis and network pharmacology. The biochemical results showed that Danshen intervention significantly reduced whole blood viscosity (WBV) at all the shear rates and fibrinogen concentration (FIB) p < 0.01 and increased activated partial thromboplastin time (APTT) effectively p < 0.01 . We also found that 52 lipid metabolites, including glycerophospholipid, sphingolipid, glycerolipid, plasmalogen, cholesterol ester, and testosterone, were associated with blood stasis. Moreover, Dgka, Hsd17b3, Hsd3b1, Inppl1, Lpl, Pik3ca, Pik3r1, Pla2g1b, Pla2g2a, Soat1, and Soat2 were predicted as potential targets, while glycerophospholipid metabolism, glycerolipid metabolism, steroid and steroid hormone biosynthesis, phosphatidylinositol signaling system, and ether lipid metabolism were involved as shared critical pathways of lipidomics analysis and network pharmacology. Collectively, this study offered a new understanding of the protection mechanism of Danshen against BSS, which provided new insight to explore the protective effects of Danshen.